The impact of COVID-19 pandemic on emotional and behavioral problems of children with autism spectrum disorder and developmental delay aged 1–6 years in China - Zhao, Yanan; Luo, Yanan; Zhang, Rong; Zheng, Xiaoying (Frontiers in Psychiatry, 2023)
The COVID-19 pandemic outbreak may cause increased levels of emotional and behavioral problems, particularly among people with pre-existing mental health conditions. Young individuals with autism spectrum disorders (ASD) and developmental delay (DD) are particularly at risk due to their vulnerability. The purpose of this study was to look into the different effects of the COVID-19 pandemic on 1–6-year-old ASD and DD children. Parents and guardians of ASD individuals completed an online survey that included questions about their children's socio-demographics and characteristics, the effects of the COVID-19 outbreak on their health, and their needs to deal with the emergency. This study characterized 4,849 preschoolers with ASD (n = 4,138), compared to preschoolers with DD (n = 711). ASD children had a higher risk of having more emotional and behavioral problems than DD children (OR 1.38, 95% CI 1.12-1.70). When compared to parent-oriented rehabilitation at home, discontinuing rehabilitation has a higher likelihood of negative emotional and behavioral change (OR 1.67, 95% CI 1.41-1.98), and having teachers' online guidance has a higher likelihood of negative emotional and behavioral change (OR 1.26, 95% CI 1.03-1.54).This work has provided evidences that children with developmental disabilities, particularly ASD, were at risk for a variety of challenges to their emotional functioning during the COVID-19 period, and that online guidance was not an ideal way for ASD children to receive effective intervention in China.